Cover Image, Volume 12, Issue 4. (5th June 2020) - Keirouz, Antonios; Chung, Michael; Kwon, Jaehoon; Fortunato, Giuseppino; Radacsi, Norbert
Abstract: The cover image is based on the Advanced Review 2D and 3D electrospinning technologies for the fabrication of nanofibrous scaffolds for skin tissue engineering: A review, by Antonios Keirouz, Michael Chung, Jaehoon Kwon, Giuseppino Fortunato and Norbert Radacsi. https://doi.org/10.1002/wnan.1626 . Abstract : The cover image is based on the Advanced Review 2D and 3D electrospinning technologies for the fabrication of nanofibrous scaffolds for skin tissue engineering: A review, by Antonios Keirouz, Michael Chung, Jaehoon Kwon, Giuseppino Fortunato and Norbert Radacsi. https://doi.org/10.1002/wnan.1626 .